Oxidative stress balance is dysregulated and represents an additional target for treating cholangiocarcinoma. (2nd July 2016) - Uchida, Daisuke; Takaki, Akinobu; Ishikawa, Hisashi; Tomono, Yasuko; Kato, Hironari; Tsutsumi, Koichiro; Tamaki, Naofumi; Maruyama, Takayuki; Tomofuji, Takaaki; Tsuzaki, Ryuichiro; Yasunaka, Tetsuya; Koike, Kazuko; et al.
ABSTRACT: Background: Pancreatico-biliary malignancies exhibit similar characteristics, including obesity-related features and poor prognosis, and require new treatment strategies. Oxidative stress is known to induce DNA damage and carcinogenesis, and its reduction is viewed as being favorable. However, it also has anti-infection and anti-cancer functions that need to be maintained. To reveal the effect of oxidative stress on cancer progression, we evaluated oxidative stress and anti-oxidative balance in pancreatic cancer (PC) and cholangiocarcinoma (CC) patients, as well as the effect of add-on antioxidant treatment to chemotherapy in a mouse cholangiocarcinoma model. Methods: We recruited 84 CC and 80 PC patients who were admitted to our hospital. Serum levels of reactive oxygen metabolites (ROM) and the anti-oxidative OXY-adsorbent test were determined and the balance of these tests was defined as an oxidative index. A diabetic mouse-based cholangiocarcinoma model was utilized to evaluate the effects of add-on antioxidant therapy on cholangiocarcinoma chemotherapy. Results: Serum ROM was higher and anti-oxidant OXY was lower in CC patients with poor outcomes. These parameters were not significantly different in PC patients. In mice, vitamin E administration induced antioxidant hemeoxygenase (HO)-1 protein expression in cancer tissue, while the number of stem-like cells increased.l -carnitine administration improved intestinal microbiome and biliary acid balance, upregulated the hepatic mitochondrial membrane uptake related gene Cpt1 in non-cancerous tissue, and did not alter stem-like cell numbers. Conclusion: Oxidative stress balance was dysregulated in cholangiocarcinoma with poor outcome. The mitochondrial function-supporting agentl -carnitine is a good candidate to control oxidative stress conditions.